MENGAWINKAN KEILMUAN: UPAYA MENGAKHIRI DIKOTOMI DAN MENGINTEGRASIKAN KEILMUAN DALAM PENDIDIKAN ISLAM - Mustakim, Zaenal (IAIN Pekalongan, 2013)
It is not foreign to us, that scientific is mapped into two recently, namely the science that focuses on religion-which came to be known as the science of religions, and scientific development that focuses on other things in general as well as the separate elements of religion in -that it be known science generally. So in practical plains, any educational institution that develops religious sciences appears on one hand and educational institutions that develop general sciences appears on the other hand. This is a 'disease' that impede the progress of our education in general, and particularly Islamic education. With full awareness, separation or dichotomy of science should immediately look for meeting point so that the subsequent development has a face that synergize with each other. Discourse and real effort to integrate this separation or dichotomy are needed. Integrating science (religion and science) is an effort that is not easy and certainly requires long time. However, with confidence and collective consciousness it is not impossible that the scientific integration will be realized and perceived benefits. In this context, it needs reconciliation in integrating scientific (read: religion and science), particularly in Islamic education.